KARAKTERISTIK PENGEMBANGAN KURIKULUM MADRASAH ALIYAH DALAM KMA 183 DAN 184 TAHUN 2019 - Megawati; Kasim Yahiji (Institut Agama Islam Hamzanwadi NW Lombok Timur, 2024)
This research aims to analyze the characteristics of curriculum development at Madrasah Aliyah based on Minister of Religion Decree (KMA) number 183 and 184 of 2019. The research method used is library research, which involves collecting and analyzing data from various relevant literature sources. The research results show that KMA numbers 183 and 184 of 2019 provide a comprehensive foundation for curriculum development at Madrasah Aliyah, with an emphasis on integration between general knowledge and Islamic religious values. However, the implementation of this curriculum faces various challenges, such as limited human resources, facilities and infrastructure, as well as a lack of understanding of curriculum policies. This research recommends the need for continuous training for teachers and improving facilities and infrastructure in madrasas. By overcoming these challenges, it is hoped that curriculum development at Madrasah Aliyah can run more effectively and efficiently, and produce graduates who are competent and have Islamic character.